Securing the internet of things: A comprehensive review of ransomware attacks, detection, countermeasures, and future prospects - Peizhi Yan; Tala Talaei Khoei (Franklin Open)
Ransomware attacks present a critical and persistent threat by denying access to data until a ransom is paid. Although existing research on IoT ransomware often concentrates on specific attack types or industry sectors, it frequently overlooks newly emerging threats and lacks holistic defense frameworks applicable across diverse IoT ecosystems. To bridge these gaps, this paper provides a comprehensive analysis of the evolving ransomware landscape targeting IoT devices. We systematically review and categorize detection technologies—ranging from signature-based methods to cutting-edge AI-driven solutions—and assess their effectiveness in mitigating these threats. Additionally, we propose a multi-layered defensive strategy integrating technological, legal, and policy measures to address the complexities of ransomware in IoT settings. Looking ahead, our study highlights potential research directions such as advancing real-time detection, leveraging blockchain for enhanced security and fostering cross-sector collaboration to bolster collective threat intelligence. By emphasizing the importance of a unified approach that involves researchers, industry professionals, and policymakers, we underline the critical steps necessary to fortify IoT infrastructures against the ever-evolving ransomware threat.